Análisis de la información proporcionada por el Gobierno Central en la toma de decisión para el cambio de semáforo frente al coronavirus (COVID-19) en el cantón Rocafuerte de la Provincia de Manabí, desde el 06 abril hasta el 03 de mayo de 2020. - Loor Pilligua, Gastón Santo (2021)
This article analyzes the information generated through the data of the infographic, the civil registry and the ECU-911, a proposal made by the National Government, for decision-making in changing the traffic light color, on the COVID-19 coronavirus pandemic. 19, in the Municipal Decentralized Autonomous Governments in Ecuador, in this case, that of the Municipal GAD of Rocafuerte, in order to demonstrate, if the information generated at the National level, were adequate or timely for decision-making in the change the color of the traffic light at the local level. In order to implement measures to reduce contagion in the canton, through a comparative and analytical study, based on data from the daily reports of the National Risk and Emergency Management System (SNGRE), Civil Registry and Integrated Security Service ECU- 911 of Ecuador, in relation to the local information of the Health District 13D12 Rocafuerte-Tosagua, Private Clinics and death certificate record of the GAD Rocafuerte, from April 06 to May 03, 2020. Finding that, the information at the local level, details information in a timely, effective and systematic manner, applying the guidelines for the analysis and development of predictive models that allow improving management, inter-institutional coordination, response, and decision-making to the corresponding authorities, since, as a result, the ranking of the communities from highest to lowest suspected cases of COVID-19 was obtained. Indicating the prioritization for care and containment strategies for COVID, while the information provided at the national level is very general, giving us a numerical number of people with suspected coronavirus, without referenced data, which does not allow us to carry out a detailed analysis, for the correct decision making, taking unequivocal scenarios. Finally, to conclude that the results show that the actions taken by the local public administration and the COE Rocafuerte, were taken through the processes based on the results of the local statistics, therefore, to prevent the spread of COVID-19, the government The local government had to exercise the integration of different institutions and inter-institutional and ministerial strategic collaboration between the public, private sectors and non-governmental organizations.